Pengaruh Nilai-Nilai Islam terhadap Kualitas Audit pada Auditor Kantor Akuntan Publik di Makassar - Syamsuddin; M. Arfin Hamid; Nasir Hamzah; Rika Dwi Ayu Parmitasari (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
Various cases of financial violations in companies that are not disclosed in the public accountant's report indicate the low quality of the audit. The cause of the low audit quality is due to the non-compliance with applicable ethical standards and auditing standards in regulating public accounting services. This study aims to determine the effect of Islamic values on audit quality. The type of research used is quantitative. This re-search was conducted on the auditors of the public accounting firm in Makassar. The sample used was purposive sampling with the criterion being that only Islamic auditors were respondents. The number of respondents who filled out the questionnaire through the google form was 146 people. Analysis of the results of qualitative research was carried out descriptively from the data information received while the analysis of quantitative research used structural equation modeling (SEM) analysis with the help of SmartPLS 3.0 soft-ware. The results showed that the value of monotheism, the value of monotheism, did not directly affect audit quality, monotheism had a direct effect on the value of the khilafah, the value of the khilafah had a direct effect on the quality of the audit and monotheism had an indirect effect on the quality of the audit through the value of the khilafah.